Upaya Guru dalam Mengimplementasikan Penilaian Portofolio di Sekolah Dasar - Amalia Putri; Muhaiminah Jalal (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2025)
Portfolio assessment is an assessment that documents the development of students over a period of time. This research aims to: (1) Know the teacher's efforts in implementing the implementation of portfolio assessment at SDN 179/X Nipah Panjang, (2) Know the supporting factors and inhibiting factors in the implementation of portfolio assessment at SDN 179/X Nipah Panjang. This type of research uses a qualitative research approach with a descriptive qualitative research type. The data collection techniques used were observation, interviews and documentation. Data were analyzed through the stages of data reduction, data presentation and conclusion drawing. The results of this study indicate that (1) Teacher efforts in implementing portfolio assessment at SDN 179/X Nipah Panjang are thorough preparation, evaluation and feedback, and teacher self-reflection, (2) Supporting factors in the implementation of portfolio assessment at SDN 179/X Nipah Panjang include school management support, collaboration between teachers, student motivation and the use of technology. Meanwhile, the inhibiting factors for portfolio assessment at SDN 179/X Nipah Panjang include time constraints and lack of teacher knowledge.